Selective formation of a phenathridine derivative by photodegradation of azilsartan. (1st June 2021) - Yoshikawa, Takahiro; Hayashi, Naoto; Hatta, Naoya; Yokota, Masayuki
Graphical abstract: Highlights: The chemical structure of photodegradation product of azilsartan was determined by alternative synthesis and single-crystal X-ray diffraction. The photodegradation product was a phenanthridine derivative. The photolysis mechanism via an imidoylnitrene intermediate has been proposed. Abstract: Photodegradation of azilsartan produces a phenanthridine derivative, with its molecular structure determined by 1 H and 13 C NMR spectroscopy. This structure is confirmed by single-crystal X-ray diffraction and alternative synthesis. The phenanthridine ring formation is explained through the ring closure of an imidoylnitrene intermediate produced by decarboxylation of the 5-oxo-1, 2, 4-oxadiazole ring (oxadiazolone).